2016
DOI: 10.1055/s-0035-1561643
|View full text |Cite
|
Sign up to set email alerts
|

Sc(OTf)3-Catalyzed Cyclization of Allyl Amides of Ethenetricarboxylate

Abstract: Catalytic cyclization of allyl amides of ethenetricarboxylate leading to pyrrolidines has been examined. Reaction of allyl amides of ethenetricarboxylate with Sc(OTf) 3 (0.2 equiv) gave 4-hydroxymethyl-2-oxopyrrolidine derivatives as major products. The formation of hydroxymethylpyrrolidines may arise from participation of adventitious water in situ. Sc(OTf) 3-catalyzed cyclization reactions of the allyl amides with TMSX (X = Cl, Br) proceeded efficiently to give halogenated 2-oxopyrrolidine derivatives. Sc(OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 4 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…A similar type of cyclization/water addition was previously observed in the Sc(OTf) 3 -catalyzed reaction of allyl amides of ethenetricarboxylate in 1,2-dichloroethane. 13…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar type of cyclization/water addition was previously observed in the Sc(OTf) 3 -catalyzed reaction of allyl amides of ethenetricarboxylate in 1,2-dichloroethane. 13…”
Section: Resultsmentioning
confidence: 99%
“…A similar type of cyclization/water addition was previously observed in the Sc(OTf ) 3catalyzed reaction of allyl amides of ethenetricarboxylate in 1,2-dichloroethane. 13 Next, the reaction of 4,4,4-trifluoro-2-butenamide 3m was examined (Scheme 8). The reaction of 3m with DBU in xylene at 140 °C or in toluene at 110 °C gave a complex mixture and the cycloadducts could not be isolated.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] The requisites of this type of cyclization are an electrophilic alkene (such as diethyl 2-arylidene malonate) bearing coordination site for metal halides and an alkyne which acts as the nucleophile. While the analogous ene-ene cyclization [7][8][9][10][11][12][13][14][15][16] is facile, enyne cyclization is less facile due to low nucleophilicity of alkyne and thus often requires highly electrophilic olefin containing three electron-withdrawing groups. Snider et al showed that in the presence of stoichiometric amount metal halide containing nucleophilic ligand such as FeCl 3 , enyne triester of type 1 undergoes intramolecular cyclization to compound 2 (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…The requisites of this type of cyclization are an electrophilic alkene (such as diethyl 2‐arylidene malonate) bearing coordination site for metal halides and an alkyne which acts as the nucleophile. While the analogous ene‐ene cyclization [7–16] is facile, enyne cyclization is less facile due to low nucleophilicity of alkyne and thus often requires highly electrophilic olefin containing three electron‐withdrawing groups. Snider et al.…”
Section: Introductionmentioning
confidence: 99%
“…Various synthetic pathways can be applied for the construction of the γ-lactam scaffold [40][41][42][43][44]. The pyrrolidinone fragment is often synthesized by transition metal- [45][46][47][48][49][50] or Lewis acidcatalyzed cyclization reactions [51][52][53][54]. The Diels-Alder reaction can also be used for the preparation of functionalized γ-lactams in a single step [55].…”
Section: Introductionmentioning
confidence: 99%